WRF-Chem simulations of ozone pollution and control strategy in petrochemical industrialized and heavily polluted Lanzhou City, Northwestern China - Li, Jixiang; Wang, Zhanxiang; Chen, Lulu; Lian, Lulu; Li, Yang; Zhao, Liuyuan; Zhou, Sheng; Mao, Xiaoxuan; Huang, Tao; Gao, Hong; Ma, Jianmin (The Science of the total environment, 2020)
As the largest petrochemical industrialized city in northwestern China since the 1950s, Lanzhou has been well-known for its heavy surface ozone pollution. Given abundant emission sources of ozone precursors and the favorable environmental conditions for O3 formation, this study performed extensive atmospheric chemistry modeling investigations subject to 11 emission control scenarios. These scenarios increased and decreased emission levels of total volatile organic compound (TVOC) and nitrogen oxides (NOx), the two surface ozone (O3) precursor gases, to examine the relationships between O3 and NOx and TVOC. The modeling investigation was carried out for the summer of 2016 in the downtown and petrochemical industrial suburb in the city of Lanzhou. The results revealed that surface O3 in the downtown area of Lanzhou was controlled by VOCs and in the petrochemical-industrialized western suburb by NOx. Higher ozone levels were simulated in the west suburb of the city as compared with the downtown area, agreeing with measured data. The relationships between modeled TVOC/NOx ratios and O3 reductions, as well as the titration effect, were also discussed. The model results provided useful references for the mitigation strategy of ozone reduction in Lanzhou and other major cities in northwest China with similar climate and topography conditions. [Display omitted] •Response of O3 pollution to precursor chemicals in Lanzhou was simulated.•Multiple precursor emission control scenarios were implemented in simulations.•Modeled O3 formation occurred in VOC and NOx control regimes in different regions.•Modeled results provided control strategies for precursor emissions across Lanzhou.